Karyotype of the South African katydid Hetrodes pupus (Linnaeus, 1758) (Orthoptera, Tettigoniidae) with special reference to relationships within the Hetrodinae subfamily - Warchałowska-Śliwa, Elżbieta; Bugrov, Alexander G. (Zootaxa, 2009)
The taxonomic position of Hetrodes pupus (Tettigoniidae, Hetrodinae) was clarified by a cytogenetic study of mitotic and meiotic chromosomes, including the localization of heterochromatin by C-banding. The karyotype of this species consists of 26 acrocentric autosomes and an acrocentric X chromosome, the largest element of the karyotype (2n male=27, FN=27; sex determination system is X0 male/XX female). A cytogenetic comparative analysis of the Hetrodinae and other katydids revealed (1) the similarity of the karyotypic features of Hetrodinae and Microtettigoninae, indicating monophyly; (2) that the morphology of the Hetrodinae karyotype is the result of parallel chromosome evolution via a decrease in the number of chromosome arms (FN).